Analisis Tingkat Pemahaman Konsep Fisika Ditinjau dari Gaya Belajar dan Gaya Berpikir Siswa - Nia Kurnia Devy; A. Halim; Muhammad Syukri; Yusrizal Yusrizal; Syahrun Nur; Ibnu Khaldun; Saminan Saminan (Jurnal Penelitian Pendidikan IPA, 2022)
There are three types of student learning styles used in the study, namely visual, auditory and kinesthetic and four types of thinking styles used in this study, namely Concrete Sequential, Abstract Sequential, Concrete Random, and Abstract Random. This study aims to analyze the level of understanding of physics concepts in terms of students' learning styles and thinking styles and examines learning styles and thinking styles that most influence the level of conceptual understanding. This study uses a quantitative approach, survey methods, and descriptive techniques. The population in this study were all students of SMAN 9 Banda Aceh, while the sample was 116 grade 2 students of SMA Negeri 9 Banda Aceh. Data analysis used descriptive statistical tests and data triangulation. The results of the analysis show that the level of understanding of students is at the second level, namely not understanding dominance compared to other levels of understanding concepts. Furthermore, it is obtained that a high kinesthetic learning style affects the level of understanding of concepts with a visual learning style. As for the thinking style, it was found that the concrete sequential thinking style was more dominant in influencing the level of conceptual understanding compared to other thinking styles